Dehydropachymic acid decreases bafilomycin A1 induced β-Amyloid accumulation in PC12 cells. (23rd February 2017) - Yu, Mengyao; Xu, Xiaoyan; Jiang, Nan; Wei, Wei; Li, Fang; He, Liming; Luo, Xia
Abstract: Ethnopharmacological relevance: Fuling, the sclerotium of Poria cocos, was frequently used in traditional Chinese medicine (TCM) formulae for Alzheimer's disease (AD) intervention over the past 10 centuries. And its extracts exhibited significant effects in both cellular and animal models of AD in previous studies. However, its mechanisms on prevention and treatment of AD have not been well elucidated yet. Aim of the study: To investigate the effect and corresponding mechanisms of dehydropachymic acid, which is one of the major triterpenes in P. cocos, on the clearance of β-amyloid accumulation in bafilomycin A1 induced PC12 cells. Materials and methods: MTT assay was used to examine the DPA effect on the viability of PC12 cells stable transfected with pCB6-APP (PC12-APP). PC12-APP cells were treated with DPA at the concentration of 6.25, 12.5, 25 μg/mL for 4 h, and then co-treated with 50 nmol/L bafilomycin A1 for 48 h except the controls. The Aβ1–42 content in culture medium was determined by ELISA. The intracellular amount of APP, Aβ1–42, LC3, cathepsin D was measured by Western blotting and normalized to GAPDH loading control. The PC12 cells stable transfected with pSelect-LC3-GFP (PC12-LC3-GFP) was used in the fluorescence microscopy estimation of autophagosomes accumulation. The internal pH in lysosome was detected by LysoTracker Red staining. Results: DPA had no significant effect on the cell viability but could significantly decrease Aβ1–42 content in culture medium and eliminate the intracellular accumulation of APP and Aβ1–42 in bafilomycin A1 induced PC12-APP cells. Furthermore, DPA lowered the LC3-II/LC3-I ratio and reduced the GFP-labeled LC3 puncta which were elevated by bafilomycin A1. And the increase in internal pH of lysosome and decrease in mCatD amount in Bafilomycin A1 induced PC12-APP cells were restored by DPA treatment. These results indicated that DPA could restore the lysosomal acidification and recover the autophgic flux which is impaired by bafilomycin A1. Conclusions: DPA could effectively clear the accumulation of Aβ1–42 in bafilomycin A1 impaired PC12 cells through restoring the lysosomal acidification and recovering the autophgic flux. And these results highlight its therapeutic potential for AD treatment. Graphical abstract: